The psychoactive pollutant fluoxetine compromises antipredator behaviour in fish. (March 2017) - Martin, Jake M.; Saaristo, Minna; Bertram, Michael G.; Lewis, Phoebe J.; Coggan, Timothy L.; Clarke, Bradley O.; Wong, Bob B.M.
Abstract: Pharmaceuticals are increasingly being detected in aquatic ecosystems worldwide. Particularly concerning are pharmaceutical pollutants that can adversely impact exposed wildlife, even at extremely low concentrations. One such contaminant is the widely prescribed antidepressant fluoxetine, which can disrupt neurotransmission and behavioural pathways in wildlife. Despite this, relatively limited research has addressed the behavioural impacts of fluoxetine at ecologically realistic exposure concentrations. Here, we show that 28-day fluoxetine exposure at two ecologically relevant dosages—one representing low surface water concentrations and another representing high effluent flow concentrations—alters antipredator behaviour in Eastern mosquitofish ( Gambusia holbrooki ). We found that fluoxetine exposure at the lower dosage resulted in increased activity levels irrespective of the presence or absence of a predatory dragonfly nymph ( Hemianax papuensis ). Additionally, irrespective of exposure concentration, fluoxetine-exposed fish entered the predator 'strike zone' more rapidly. In a separate experiment, fluoxetine exposure reduced mosquitofish freezing behaviour—a common antipredator strategy—following a simulated predator strike, although, in females, this reduction in behaviour was seen only at the lower dosage. Together, our findings suggest that fluoxetine can cause both non-monotonic and sex-dependent shifts in behaviour. Further, they demonstrate that exposure to fluoxetine at environmentally realistic concentrations can alter antipredator behaviour, with important repercussions for organismal fitness. Graphical abstract: Highlights: Mosquitofish ( G. holbrooki ) exposed to fluoxetine (FLX) at two realistic levels. FLX at the lower level increased activity in the presence or absence of a predator. FLX at both levels reduced latency to enter predator strike zone. FLX caused sex-dependent reduction in 'freezing' after a simulated predator strike. Exposure to FLX can have detrimental sub-lethal impacts on antipredator behaviour. Abstract : Fluoxetine exposure at two environmentally realistic concentrations impairs multiple aspects of antipredator behaviour in mosquitofish ( Gambusia holbrooki ).